Does a web-based decision aid improve informed choice for fertility preservation in women with breast cancer (DECISIF)? Study protocol for a randomised controlled trial. Issue 2 (10th February 2020) - Benoit, Alexandra; Grynberg, Michael; Morello, Rémy; Sermondade, Nathalie; Grandazzi, Guillaume; Moutel, Grégoire
Abstract : Introduction: Chemotherapy may cause infertility in young survivors of breast cancer. Various fertility preservation techniques increase the likelihood of survivors becoming genetic mothers. Disclosure of cancer diagnosis may impact decision making about fertility preservation. This protocol will develop and test the effectiveness of a web-based decision aid for helping women with breast cancer to make well-informed choices about fertility preservation. Methods and analysis: This study will be conducted in three phases using mixed methods. In phase I, the aim is to develop a web-based patient decision aid (PDA) in French with a steering committee and using a focus group of five women already treated for breast cancer. In phase II, the face validity of the decision aid will be assessed using questionnaires. In phase III, the PDA will be assessed by a two-arm randomised controlled trial. This will involve a quantitative evaluation of the PDA in clinical practice comparing the quality of the decision-making process between usual care and the PDA. The primary outcome will be informed choice and its components. The secondary outcomes will be decisional conflict and anxiety. Data will be collected during and after an oncofertility consultation. Phase III is underway. Since September 2018, 52 participants have been enrolled in the study and have completed the survey. We expect to have results by February 2020 for a total of 186 patients. Ethics and dissemination: This study protocol was approved by the Ouest V Research Ethics Board. Results will be spread through peer-reviewed publications, and reported at suitable meetings. Trial registration number: The ClinicalTrials.gov registry .(NCT03591848 ).